Empowering Community: Theatre of the Oppressed as a Tool of Homeless People’s Emancipation - Černá, Eliška; Polánková, Lenka (Participatory Social Work: Research, Practice, Education, 2019)
In the chapter we describe a process and outcomes of a research project which aimed to find out knowledge about “social housing” for those who are poor, and how we can co-produce, within what action strategies, such knowledge. We take pedagogy of the oppressed as a theoretical grounding. Emancipatory action research is chosen as a research design, specifically theatre of the oppressed: a participatory methodology that can be used for knowledge co-production. In the chapter, we introduce screenplay of theatrical performance Having Home Means Being Housed!. Further, we present business with poverty in flats as a central theme. Specific action strategies were co-developed while performing the play. Key common issues identified within them are decisions not to give up, building solidarity and making the problem public. In the final part of the chapter we discuss the use of theatre of the oppressed as a tool of empowering marginalised communities.